Peran Proyeksi Pemeriksaan Cystography dengan Klinis Batu Buli di Instalasi Radiologi RSPAU dr. Suhardi Hardjolukito - Meilani Dwi Putri; Widya Mufida; Dyah Ayu Puspitaningtyas (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Cystography examination technique with clinical Bladder Stone in the Radiology Installation of RSPAU dr. Suhardi Hardjolukito in the AnteroPosterior (AP) projection uses a perpendicular vertical beam direction. Meanwhile, according to Lampignano & Kendrick, (2018) Cystography examination in the AnteroPosterior (AP) projection, the beam direction is angled 10˚-15˚ towards the caudad. The purpose of this study was to determine the Cystography examination procedure and the role of the antero posterior (AP) projection in cystography examination with clinical bladder stone using a perpendicular beam direction to the image receptor in the Radiology Installation of RSPAU dr. Suhardi Hardjolukito. This research method uses qualitative descriptive with a case study approach. This research was conducted at the Radiology Installation of RSPAU dr. Suhardi Hardjolukito from March to May 2025. The objects in this study were patients undergoing Cystography examination, with the research subjects consisting of one patient who experienced a case of Batu Buli. After the data was reduced, the data presentation was carried out in narrative form and then reviewed with a theoretical basis so that conclusions could be drawn. The results of this study indicate that the examination procedure for Cystography with clinical Batu Buli at the Radiology Installation of RSPAU dr. Suhardi Hardjolukito includes patient preparation, preparation of tools and materials, examination techniques, and gradual injection of contrast media. The gradual administration of contrast medium is effective for monitoring the patient's condition and preventing complications such as bladder rupture. This modification of the technique demonstrates that standard procedures can be adapted while maintaining optimal diagnostic quality.